Temperature and Humidity Control in a Small-Scale Greenhouse in a Tropical Climate - Aditya A. Jamaluddin, Tisha; Sitti Nur, Faridah; Muhammad Tahir, Sapsal; Dani Achmad, Andini; Reskyanto , Ari (Program Studi Teknik Pertanian Universitas Hasanuddin, 2025)
Global climate change has increased fluctuations in temperature and humidity, threatening the sustainability of the agricultural sector. This research aimed to develop an Internet of Things (IoT)-based microclimate control system for greenhouses using Arduino and the Thingspeak platform. The system was designed as a closed-loop using an ESP-32 as the control center, a DHT-22 sensor for data acquisition, and Solid-State Relay (SSR) actuators to control the blower, heater, and misting pump. Testing was conducted in a greenhouse with an area of 3 m² and a height of 2.3 meters. The results showed that the system could maintain a temperature of 27–36°C (external deviation: 29–48°C) and humidity of 85–90% (external deviation: 47–100%) with low overshoot, namely 1.18% (temperature) and 1.49% (humidity), and a settling time of under 4 minutes. The steady-state error was within the tolerance limit (maximum 5%). However, the system experienced a data loss of 26.04% and an average transmission delay of 16.5 seconds due to network instability at the test location. Nevertheless, the system proved effective in maintaining an optimal microclimate for small-scale plant growth.